2008
DOI: 10.1002/ase.33
|View full text |Cite
|
Sign up to set email alerts
|

Self‐directed learning in gross human anatomy: Assessment outcomes and student perceptions

Abstract: Speech pathology students enrolled in a lecture-based gross human anatomy program completed two out of nine topics in self-directed mode. Student performance in quizzes was compared for the two modes, and the students completed questionnaires on their perceptions of the self-directed mode of delivery. Students performed as well in the first self-directed topic as they did in lecture-based material, but performance declined significantly on the second self-directed topic. Correlations showed that students who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
(16 reference statements)
0
20
0
1
Order By: Relevance
“…This decline was observed in both of this studies and has been reported to occur with practice quizzes ) and the use of other voluntary course resources whether it is an audience response system (Hoyt et al, 2010) or an online dissector (Mc Nulty et al, 2004). These declines may be the result of students discovering that a specific resource does not fit their learning style and/or increasing demands on their time as the course progresses (Smythe and Hughes, 2008). One objective of our study was to determine optimal times to give practice quizzes.…”
Section: Discussionmentioning
confidence: 99%
“…This decline was observed in both of this studies and has been reported to occur with practice quizzes ) and the use of other voluntary course resources whether it is an audience response system (Hoyt et al, 2010) or an online dissector (Mc Nulty et al, 2004). These declines may be the result of students discovering that a specific resource does not fit their learning style and/or increasing demands on their time as the course progresses (Smythe and Hughes, 2008). One objective of our study was to determine optimal times to give practice quizzes.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although students typically prefer active learning compared to lectures, some evaluations have shown unfavorable effects with certain active-learning techniques. 27,28 Active learning is more about engaging the student than a specific process 29 ; thus, self-testing should qualify as active in the sense that it engages students and provides them correctives for their metacognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…This decline was observed in both of this studies and has been reported to occur with practice quizzes (Kibble et al, ) and the use of other voluntary course resources whether it is an audience response system (Hoyt et al, ) or an online dissector (McNulty et al, ). These declines may be the result of students discovering that a specific resource does not fit their learning style and/or increasing demands on their time as the course progresses (Smythe and Hughes, ).…”
Section: Discussionmentioning
confidence: 99%